Using Cooperative Integrated Reading and Composition to Teach Writing - Zahratul Idami (Universitas Syiah Kuala, 2015)
This study was conducted to investigate the effect of the use of Cooperative Integrated Reading and Composition (CIRC) technique in teaching writing to the second grade students at a junior high school in Muara Batu, North Aceh. An experimental design was used in this study and the data was collected through tests as the instrument. Two classes of the second grade were taken as the sample for this study. The experimental class (EC) had 28 students and there were 30 students in the control class (CC). The findings showed that using CIRC technique positively affected the writing scores of the students. The students in EC got higher writing scores (x ̅ = 85.75) than those of the students in CC (x ̅ =72.267). Furthermore, students’ writing ability in both classes was different as indicated by the t-test. The result from t-test was 5.08. Whilst the result from t-table at the level of significance 5% (α = 0.05) was 2,012. Thus the t-test result is higher than t-table (5.08 2.00654). Thus, it can be concluded that the students who were taught through CIRC got better results in writing than those who were taught through the conventional individual writing activity method.